Pediatric Obesity's Effect on Open and Laparoscopic Appendectomy Outcomes - Bhatnagar, Anshul; Nigam, Nishtha; Anne, Rohan; Santosh, Sadashiv (The Surgery Journal, 2024)
Background Pediatric obesity is a common comorbid condition that may complicate pediatric surgeries, such as appendectomy. Prior research on the consequences of obesity on pediatric appendectomy outcomes have been limited by small-sample sizes and pooled analyses that do not distinguish the effects of surgical approach. Associations between surgical approach, pediatric obesity, and postoperative appendectomy outcomes thus remain unclear.Objective To analyze postoperative appendectomy outcomes by accounting for pediatric obesity, appendectomy approach, and their interaction. This is a retrospective cohort population analysis. Nationwide data of pediatric inpatients from the United States were obtained. All pediatric patients who had an appendectomy were selected from the 2019 Kids' Inpatient Database.Materials and Methods Outcomes variables were the length of stay and postoperative complication rate. The primary exposure variables were pediatric obesity, surgical approach (laparoscopic [LA] vs. open appendectomy [OA]), and an interaction term between the two. Control variables were patient demographics, clinical complexity, and geographic location. Multiple regression was used to determine relationships between the outcome, exposure, and control variables.Results A total of 49,037 pediatric patients had an appendectomy, with the number of OA and LA being 4,517 and 44,420, respectively. LA patients had 5.8% (p < 0.001) shorter length of stay than OA patients. For obese patients, length of stay was 31.8% (p < 0.001) longer than for nonobese patients, but LA (compared with OA) reduced it by 19% (p < 0.007). Obesity had no effect on the number of postoperative complications.Conclusion Obese patients had significantly longer length of stay than nonobese counterparts following OA (31.8%), but this difference was minimized for LA patients (15.81%). There was no association between complication rate, obesity, and surgical approach. Our findings will enable more accurate estimations of pediatric patients' postoperative courses and efficient allocation of limited hospital resources. Further research may wish to study the effects of other common pediatric comorbidities on other procedures.
Keywords: laparoscopic appendectomy; open appendectomy; obesity; length of stay; postoperative complications; regression